2015
DOI: 10.1001/jamaophthalmol.2015.3888
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Among Ocular Pathogens in the United States

Abstract: IMPORTANCE The Antibiotic Resistance Monitoring in Ocular Microorganisms (ARMOR) study is the only ongoing nationwide antibiotic resistance surveillance program specific to ocular pathogens. OBJECTIVE To report resistance rates and trends among common ocular isolates collected during the first 5 years of the ARMOR study. DESIGN, SETTING, AND PARTICIPANTS This antibiotic resistance surveillance study was performed at an independent central laboratory. Clinical centers across the United States were invited to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
72
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 48 publications
(14 reference statements)
17
72
1
3
Order By: Relevance
“…Overall these three organisms did not show alarming resistance to the antimicrobials tested and are consistent with other antimicrobial surveillance studies that have been conducted recently [1, 7, 13, 19]. …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall these three organisms did not show alarming resistance to the antimicrobials tested and are consistent with other antimicrobial surveillance studies that have been conducted recently [1, 7, 13, 19]. …”
Section: Discussionsupporting
confidence: 89%
“…There have been a few nationwide surveillance studies, such as Ocular TRUST and ARMOR, which have tracked resistance patterns in many common ocular pathogens [9, 13]. However, given the growing importance of this issue, there is also a need for smaller, regional studies to obtain local data.…”
Section: Introductionmentioning
confidence: 99%
“…Eighty-one percent of the indefinable ( n = 216) P. aeruginosa isolates from the ARMOR study were from the cornea. [11] BPEI data for 2011-2015 mirrored these results.…”
Section: Resultsmentioning
confidence: 63%
“…7,9 However, increasing degrees of antimicrobial resistance in gram-negative organisms is a concern in other parts of the world. In the EVS, 89.5% of gram-negative bacteria were sensitive to both amikacin and ceftazidime.…”
Section: Emerging Worldwide Antimicrobial Resistancementioning
confidence: 99%
“…6 In 1999, Kunimoto et al from India reported incomplete susceptibility of gram-negative isolates for ciprofloxacin (87.5%), amikacin (82.1%) and ceftazidime (60.9%). 9 Also Dave et al in 2016 reported 11 cases of endophthalmitis from India caused by ceftazidime-resistant gram-negative organisms. These cases were subsequently managed with intravitreal imipenem.…”
Section: Emerging Worldwide Antimicrobial Resistancementioning
confidence: 99%